Assessment of the Phytochemical Composition and Antioxidant Properties of Ripe Fruit of Cucumis metuliferus E. Meyer Ex. Naudin - Usman, Joy Gararawa; Gadzama, Usman Ngamarju; Elisha, Ishaku Leo; Onakpa, Monday Michael; Ajagbonna, Olatunde Peter; Sanni, Saka (Pharmacognosy Communications)
Background: Plants' secondary metabolites have great potential as anti-oxidants for slowing or alleviating various diseases. Cucumis metuliferus E. Mey. Ex. Naudin Curcubitaceae has been consumed by man and animals as food and used as alternative treatment for some diseases by traditional farmers. However, there is little information on its phytochemical composition and antioxidant properties. This study was carried out to investigate the quantitative phytochemicals and in vitro anti-oxidant activity of the ripe fruits of Cucumis metuliferus using DPPH radical scavenging assays. Materials and Methods: The ripe fruits of Cucumis metuliferus were collected on the parent plants in Vom, Jos South Local Government, Plateau State and were dried at room temperature. The ground powder of Cucumis metuliferus was made and divided into 3 portions. The first portion was extracted using 80% methanol: distilled water (80:20) to obtain the 80% methanol extract. The second portion of the ground fruits was extracted using distilled water to obtain the Aqueous Extract (AE). The third portion of the ground fruits was sequentially extracted with solvents of different polarities. First, n-hexane was used and the marc from n-hexane was air-dried and then extracted using chloroform, followed by ethyl acetate, methanol and water in that order (each time drying the marc for the subsequent extraction) to obtain the HE, CE, EAE, ME and RE extracts respectively. The extracts were screened for secondary metabolites and evaluated for their in vitro anti-oxidant activity using DPPH radical reduction assays. Results: The Cucumis metuliferus extract contained carbohydrates, cardiac glycosides, flavonoids, steroids, quinones, coumarins, lignins, phenols, alkaloids, phlobatannins, saponins, tannins, terpenoids and volatile oils. The extracts showed anti-oxidant activity, with IC50 values ranging between 537.56-2579.91 μg/mL. Conclusion: The presence of these phytochemical classes in the ripe Cucumis metuliferus fruit and the relatively high anti-oxidant activity reported in this study supports its folkloric use in the treatment of diseases and as an anti-oxidant agent.
Keywords: Phytochemical screening; DPPH; Anti-oxidant activity; Cucumis metuliferus.